2005
DOI: 10.1016/j.canlet.2004.07.022
|View full text |Cite
|
Sign up to set email alerts
|

A wide role for NOTCH1 signaling in acute leukemia

Abstract: NOTCH1 is involved in the pathogenesis of T-acute lymphoblastic leukemia (T-ALL) carrying the very rare translocation t(7;9)(q34;q34.3). We analyzed the expression of genes belonging to NOTCH pathway, in acute leukemia primary samples and lymphoblastoid cell lines. NOTCH1 pathway activation represents a common feature of T-ALL when compared to acute myelogenous leukemia (AML) and B-cell precursor acute lymphoblastic leukemia. The contemporary expression of NOTCH1 and its ligands on cell surface contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…The involvement of Notch pathway in B-cell malignancies is not well understood. In general, BCP-ALLs show lower NOTCH expression than T-ALLs (Chiaramonte et al, 2005), whereas B-cell derived Hodgkin lymphoma cells showed overexpression of both NOTCH and JAG1 (Jundt et al, 2002). Larger studies and further functional analyses are needed to understand the biological role of JAG1 up-regulation in ETV6-related leukemia, and to define whether this aberration is related to the isolated ETV6 deletion, in association with the t(12;21) translocation or with the chromosome 21 aberrations (iAMP21 or trisomy 21).…”
Section: Discussionmentioning
confidence: 94%
“…The involvement of Notch pathway in B-cell malignancies is not well understood. In general, BCP-ALLs show lower NOTCH expression than T-ALLs (Chiaramonte et al, 2005), whereas B-cell derived Hodgkin lymphoma cells showed overexpression of both NOTCH and JAG1 (Jundt et al, 2002). Larger studies and further functional analyses are needed to understand the biological role of JAG1 up-regulation in ETV6-related leukemia, and to define whether this aberration is related to the isolated ETV6 deletion, in association with the t(12;21) translocation or with the chromosome 21 aberrations (iAMP21 or trisomy 21).…”
Section: Discussionmentioning
confidence: 94%
“…These data were confirmed by quantitative PCR. The Notch-signaling cascade and its ligand JAG1 are involved in maintenance and renewal of hematopoietic stem cells and have been described as deregulated in various malignant hematopoietic disorders [41][42][43][44][45]. Stirewalt et al recently identified JAG1 expression changes in leukemic blasts compared with hematopoietic cells from healthy donors with subsequent confirmation of an increased expression of JAG1 using microarray data from 285 AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Jagged1, Jagged2, Notch1 and Notch2 proteins are found in samples of human multiple myeloma (15). Acute myelogenous leukemia (AML) is characterized by overexpression of Jagged1 mRNA/protein and Notch1 protein (16). Two recent studies have identified activating Notch1 mutations in chronic lymphocytic leukemia (CLL) (17,18).…”
Section: Notch Signaling Pathway Its Components and Their Role In Camentioning
confidence: 99%